Reframing Islamic Edupreneurship in Primary Teacher Education: A Critical Perspective on Outcome-Based Education - Siti Rofi'ah; Jasminto; Ali Mahsun; Maidatus Sa'diyah; Vian Hanes Andreastya; Imam Muslih; Resdianto Permata Raharjo (MUMTAZ : Jurnal Pendidikan Agama Islam, 2026)
This study critically examines the integration of edupreneurship into the curriculum of the Madrasah Ibtidaiyah Teacher Education (PGMI) program at Universitas Hasyim Asy’ari (UNHASY), framed within the Outcome-Based Education (OBE) approach and informed by critical theory. The urgency of this research stems from the growing pressure on Islamic higher education institutions to respond to global economic demands while simultaneously preserving the spiritual-ethical identity of Islamic education. In this context, the incorporation of edupreneurship into teacher education raises fundamental questions about how economic competencies can be harmonized with the moral, social, and cultural values rooted in pesantren traditions. Employing a qualitative methodology comprising document analysis, classroom observations, and in-depth interviews the research identifies a persistent tension between the technocratic orientation of OBE and the emancipatory vision of Islamic education. While the curriculum embeds entrepreneurial competencies within learning outcomes and course structures, its implementation tends to prioritize technical outputs over the cultivation of spiritual-ethical values. Nevertheless, evidence of cultural resistance emerges through students and lecturers who uphold pesantren-based ethics such as sincerity (ikhlas), social responsibility, and barakah (divine blessing). The study concludes that Islamic edupreneurship must be critically safeguarded to prevent its reduction to mere economic instrumentalization, ensuring instead that it functions as a vehicle for social transformation, community empowerment, and the preservation of Islamic educational ideals.